National language and national media: problems of popularization and development - Magdana Z. Mantashashvili, Murshida H. Fatykhova, Elena S. Doroschuk, (Opción, 2019)
The article aims to investigate the problems of popularization and development of national language and national media via the quantitative analysis of the Tatar-speaking mass media on the territory of Russia and the Republic of Tatarstan. As a result, the tasks of Tatar language promotion and development are solved through the creation and the development of a balanced system of national media. In conclusion, this system is based on the principles of the national rhetorical ideal consideration, the key psycho-mental characteristics of the ethnos, speech means, presenting the national axiology and the features of national culture presentation.